Pengaruh Motivasi Kerja, Kompetensi Dan Kompensasi Terhadap Kinerja Karyawan Yayasan Pendidikan Islam Ummul Quro Al-Muqaromah Karawang - Aminudin Aminudin (Journal of Economic, Bussines and Accounting (COSTING), 2023)
The purpose of this study is to determine, explain and analyze the effect of work motivation, competence and compensation on employee performance, as well as the partial and simultaneous effect of work motivation, competence and compensation on employee performance. The population is 120 and a sample of 92 respondents is taken using the Slovin formula. This research method uses descriptive and verification methods. The results of the study indicate that work motivation has a positive and partially significant influence on employee performance, which is 10.2%. Competence has a positive and significant influence partially on employee performance, which is 15.1%. Compensation has a positive and partially significant effect on employee performance, which is 36.4%. And there is a simultaneous positive and significant influence between Work Motivation, Competence and Compensation on Employee Performance. The total simultaneous effect of work motivation, competence and compensation on employee performance is 61.8%, while the remaining 38.2% is the influence of other variables (É›) which were not examined. Keywords: Work Motivation, Competence, Compensation, Employee Performance